Prefabrication of Vascularized Bone Allograft in a Recipient Rat Using a Flow-through Vascular Pedicle, Bone Morphogenetic Protein, and Bisphosphonate - Nakamura, Osamu; Kaji, Yoshio; Imaizumi, Yasuhiko; Yamagami, Yoshiki; Yamamoto, Tetsuji (Journal of Reconstructive Microsurgery, 2013)
We attempted to prefabricate vascularized bone allografts by implanting flow-through vascular bundles from recipient rats into transplanted bone allografts. We also applied bone morphogenetic protein (BMP) and bisphosphonate into the bone allograft to accelerate bone formation and inhibit bone resorption in the transplanted bone. After prefabrication, bone formation and resorption in the vascularized bone allograft were evaluated radiographically and histologically. We also attempted to transfer the prefabricated vascularized bone allograft onto the femur of recipient rats, and bone union between was subsequently assessed. Bone formation in the transplanted allograft was significantly stimulated with addition of BMP. However, bone resorption was also stimulated by BMP; this stimulated bone resorption caused by BMP was effectively inhibited with addition of bisphosphonate. The bone union rate between transplanted bone allografts and recipient femora was also stimulated by BMP. Bisphosphonate slightly delayed bone union but effectively protected the grafted bone from bone resorption caused by BMP. Our results suggest that prefabrication of vascularized bone allografts can be achieved in the recipient rat by implanting a flow-through vascular bundle from the recipient into the transplanted bone allograft. Combination treatment with BMP and bisphosphonate allows development of an ideal vascularized bone allograft.
Keywords: prefabrication; allograft; bone morphogenetic protein; bisphosphonate